Pengaruh Desain Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Ketahanan Pangan Kabupaten Musi Banyuasin (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT The problem in this study is whether there is an influence of work design and work environment partially or simultaneously on employee performance at the Food Security Service of Musi Banyuasin Regency. The purpose of this study was to determine the influence of work design and work environment partially or simultaneously on employee performance at the Food Security Service of Musi Banyuasin Regency. The method used in this study is a quantitative method. Data collection techniques were carried out by interviews, observations, and questionnaires. The data analysis techniques used were classical assumption tests, multiple linear regression tests, hypothesis tests, and determinant coefficient tests. Based on the results of the study, it can be seen that 1) there is no significant influence of Work Design on the Performance of the Food Security Service of Musi Banyuasin Regency. This is evidenced by a significance value of -0.731> 0.05. The coefficient value  = -0.185 which means that the more the work design decreases, the employee performance will decrease; 2) there is a significant influence of the Work Environment on the Performance of the Food Security Service of Musi Banyuasin Regency. This is proven by the significance value of 0.000